Effect of Vitamin D deficiency and some hematological parameters in Iraqi female patients with Systemic Lupus Erythematosus - Ekhlass Noori Ali; Ranya Hasan Hussein; Sabaa Taher Mohammed; Hamzia Ali Ajah (Tikrit Journal of Pure Science, 2024)
Background: Systemic Lupus Erythematosus (SLE) is a chronic inflammatory autoimmune disease that affects multiple organs. Vitamin D deficiency is considered potential environmental factor triggering some autoimmune disorders, including SLE. This study was performed for determination of effect of vitamin D deficiency in SLE infection or disease worsening, and the relationship of ESR, HB, and WBCs with level of vitamin D in SLE disease, in addition to determine which of the previous parameter may describe the disease case of patients.